Managing in a time of great change - Drucker, Peter F. (Peter Ferdinand) 1909-2005 (Truman Talley Books, 1995)
The nation's top management guru offers advice to executives for thriving in the global business environment of the future, covering such topics as team building, cutting costs in retail, changes in the U.S. economy, and doing business in Japan.